From Hype To Habit: Decoding Eco-Literacy and Digital Driven Premium Demand For Sustainable Products - Daranti Rahmadhani; Ramadania Ramadania; Harry Setiawan; Juniwati Juniwati; Ana Fitriana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the influence of Digital Green Marketing (DGM), Green Perceived Value (GPV), and Environmental Concern (EC) on consumers’ Willingness to Pay Premium Price (WTPP) in Indonesia, with Eco-literacy (EL) as a moderating variable. Using a quantitative approach with 200 respondents aged 18–30 and analyzed SEM-PLS, the results show that DGM, GPV, and EC have a significant positive effect on WTPP. Furthermore, Eco-literacy significantly strengthens all relationships between the independent variables and WTPP, indicating its critical role in transforming environmental awareness into actual economic commitment.These findings suggest that although consumers are increasingly exposed to sustainability issues, their willingness to pay premium prices depends not only on marketing exposure and perceived value but also on their level of environmental understanding. This study contributes to the literature by highlighting eco-literacy as a key boundary condition in sustainable consumption behavior. Practically, it emphasizes the importance of integrating educational elements into digital green marketing strategies to enhance consumer willingness to support sustainable products.